Urban Health and Wellness in Indian Context - A Strategic Approach in Urban Design. (2016) - Rajan, Asha; Manoj Kumar, K.
Abstract: The transformation of man from a nomadic culture to a sophisticated being has brought him detached from his so called 'nature' to 'cubicle'. This withdrawal from nature and natural essence to artificial environment (prolonged use of urban built environment) has caused not only external changes to his environment, but also internally as like health challenges – Life style diseases. Several pathways have been identified in the research linking built environments with travel patterns, activity levels, vehicle emissions, body weight, and associated causes of death and disability in India. At this point it is highly recommended that we analyses the link between disease burdens of India and its causing factors, in an urban designer's perspective as it has created a curiosity in the wisdom of an urban designer. Thus we could arrive at a point from where we can judge these factors by disintegrating it into smaller parameters which are easier to be analyzed and in turn help us to optimize and to negate these ill effects. Though India has great traditional knowledge systems in health care sector and life style through teachings of great civilizations[1], latest studies in health sector reveal that, we have moved away from our culture and tradition and facing acute and chronic diseases including non-communicable diseases, infectious diseases and violence (mental disorders and injuries) Hence, there should be sincere effort to bridge the existing gap between urban development and health wellness urban design interventions..